Preferential expression of AChR epsilon-subunit in thymomas from patients with myasthenia gravis. - Maclennan, C; Vincent, A; Marx, A; Willcox, N; Gilhus, N; Newsom-Davis, J; Beeson, D (2008)
The role of antigen expression by thymomas in myasthenia gravis (MG) is not clear. Previous reports of acetylcholine receptor (AChR) mRNA expression by the highly sensitive reverse transcription-polymerase chain reactions (RT-PCR) produced varying results. To try to clarify this issue, we first used RT-PCR but then turned to the more accurate and quantitative RNase protection assays (RPA) to assess AChR subunit mRNA expression in thymomas from 25 patients (22 with MG). By RT-PCR, all five AChR subunits could be detected in many thymomas. However, by RPA, the mRNA for the adult-specific AChR epsilon-subunit was found in 13/25 (52%) thymomas, but not mRNA for the other subunits. AChR epsilon-subunit was more frequently detected in thymomas of A or AB histology (WHO classification) than those with B1-B3 histology. Overall, 6/6 with thymomas of A or AB histology were positive compared with only 8/19 with B histology (p=0.02). Autoantibodies in the two patients with the highest levels of epsilon-subunit mRNA bound better to adult (alpha(2)betadeltaepsilon) AChR than to fetal (alpha(2)betadeltagamma) AChR, whereas the other sera bound better to fetal AChR. The greater abundance of mRNA for AChR epsilon-subunit than for other subunits suggests that the AChR epsilon-subunit may play a distinctive role in autosensitization in MG-associated thymomas, particularly those of type A or AB.